2007
DOI: 10.1016/j.joen.2006.11.026
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antibacterial Efficacy of Ultrasound after Hand and Rotary Instrumentation in Human Mandibular Molars

Abstract: The purpose of this prospective, randomized, single-blind study was to compare the in vivo antibacterial efficacy of a hand/rotary technique versus a hand/rotary/ultrasound technique in mesial root canals of necrotic mandibular molars. The hand/rotary group consisted of 16 mesial roots prepared with a hand/rotary technique. The hand/rotary/ultrasound group consisted of 15 mesial roots prepared similarly, followed by 1 minute of ultrasonic irrigation per canal with an ultrasonic needle in a MiniEndo unit and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
17

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 35 publications
2
92
0
17
Order By: Relevance
“…However, neither method addresses a potential confounder variable that is the influence of the apical anatomy on the potential extrusion of the irrigating solution. The apical third of the root has reportedly the highest incidence of accessory canals and apical deltas 32,23) . In addition, accessory apical foramina have also been shown to exist in mandibular molars 34) and could very well be present in other teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, neither method addresses a potential confounder variable that is the influence of the apical anatomy on the potential extrusion of the irrigating solution. The apical third of the root has reportedly the highest incidence of accessory canals and apical deltas 32,23) . In addition, accessory apical foramina have also been shown to exist in mandibular molars 34) and could very well be present in other teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CUIS (CUI with saline) was able to completely remove the SL at the coronal level in 5 specimens that might be due to the ultrasonication, it was unable to remove the SL more apically. Previous studies revealed that ultrasonic irrigation cannot get through the apical area due to vapor lock 23,44) . However, with the aid of NaOCl, results showed the maximum SL removal in the apical third was attained equally with the EV and CUI (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the much higher velocity and volume of irrigant flow that are created in the canal during ultrasonic irrigation. Ultrasonics can effectively clean debris and bacteria from the root canal system, but cannot effectively get through the apical vapor lock [31][32][33].…”
Section: Ultrasonic Irrigationmentioning
confidence: 99%
“…Recently, with its gradually increasing popularity, passive ultrasonic activation of endodontic instruments has been suggested as a means to improve canal debridement [13], canal disinfection [14] and canal sealing [15]. Passive ultrasonic irrigation (PUI) has also been recommended for removing Ca(OH) 2 from the root canal [16].…”
Section: Introductionmentioning
confidence: 99%